2019
DOI: 10.1016/j.ejpoleco.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in space: A closer look at the world's subnations

Abstract: The level of corruption differs not only between countries, but also between subnations within countries. In this paper we analyze spatial interdependencies in corruption levels for a large sample of 1,232 subnations in 81 countries. Based on a spatial autoregressive model, which additionally corrects for spatial autocorrelation in the error term, we find that a subnation's corruption level is positively affected by neighboring subnations' corruption levels. This suggests that subnational corruption levels are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 87 publications
0
28
0
Order By: Relevance
“…Related studies by Becker et al (2009), Faber and Gerritse (2012), Jetter and Parmeter (2018), and Borsky and Kalkschmied (2019) have shown that corruption in an individual country or region is positively correlated with corruption in neighboring countries or regions.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Related studies by Becker et al (2009), Faber and Gerritse (2012), Jetter and Parmeter (2018), and Borsky and Kalkschmied (2019) have shown that corruption in an individual country or region is positively correlated with corruption in neighboring countries or regions.…”
Section: Resultsmentioning
confidence: 92%
“…This strategy is motivated by the regional concentration of corruption. Corruption in an individual country has been shown to be positively correlated with corruption in neighboring countries; there is spatial dependence between and within countries (e. g., Becker et al 2009 Borsky and Kalkschmied (2019).…”
Section: Endogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study Borsky showed that "Our estimation results indicate that subnational corruption levels are, due to spatial interdependencies and spatial heterogeneity, significantly correlated in space [8]. Spatial interdependencies and feedback effects stemming from a marginal change in an independent variable are about the same size as direct effects.…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, the public prosecutor understands the meaning of the actus and mens rea in eradicating corruption, so it is almost certain that no suspect will win in the pre-trial forum or the defendant is convicted by the court (Borsky and Kalkschmied, 2019). Because investigators have ensured that the perpetrators' actions are possessed of dolus malus, the perpetrators are to blame and cause consequences in the form of state financial losses.…”
Section: Judge's Considerations In the Context Of Mens Reamentioning
confidence: 99%